Blended Learning for Long-Lasting Education: Benefits and Constraints of Blended Learning Implementation on ELT - Salvida Yunita; Asnawi Muslem; Saiful Marhaban (Proceedings of AICS - Social Sciences, 2021)
This qualitative research aimed to discover the benefits and constraints of Blended Learning faced by English as a Foreign Language (EFL) teachers in teaching English. In total, 65 pieces of studies were analyzed by using tables and charts which are categorized based on the content of the research reports. Both quantitative and qualitative analysis were employed to analyze the data. Then, the data were computerized and processed using Microsoft Excel to see the distribution of each classification. There were fourteen tables of Paper Classification Form (PCF) classified in this study. The result shows that the Blended Learning (BL) model lists numerous advantages for both teachers and students. Moreover, the benefits of BL were categorized in terms of benefits for students, teachers, and pedagogy. However, there were few articles that described the constraints faced by the teachers and students during the implementation of BL such as the limitation of Internet access, the requirement of creative activities, and the problems with the students who have low motivation in learning.Keywords: Blended Learning models, English language teaching, research reports